Investigation of focused wave impact on floating platform for offshore floating wind turbine : a CFD study - Zhou, Yang; Xiao, Qing; Liu, Yuanchuan; Incecik, Atilla; Peyrard, Christophe (2019)
Most existing research related to a semi-submersible offshore floating platform focuses on the wave-structure interaction under either a regular or irregular wave condition. In order to numerically model the irregular wave impact on a semi-submersible platform hydrodynamic response with a low computational cost, in this study, a focused wave is utilized. The platform under this consideration is the DeepCwind semi-submersible platform. A high fidelity CFD numerical solver based on solving Navier-Stokes equations is adopted to estimate the dynamic response and the hydrodynamic loading of the platform. The focused wave is firstly generated based on a first order irregular wave theory in a numerical wave tank and validated against the linear wave theory results. Next, for CFD coding validation, the surface elevation of a fixed FPSO model associated with a focused wave is calculated and compared with the benchmark results. At last, the dynamic responses of the platform are numerically simulated under various focused wave parameters, and the results are compared with those obtained from an in-house potential flow theory tool at Électricité de France (EDF). It is found that the predicted CFD surge motion responses are close to those achieved with the second order potential theory while differ from the results obtained using linear potential theory. As to the pitch motion, differences are observed between two results, due to the different methods used for second order loads and viscous effects calculation. Turning to the results under different wave parameters, the surge and heave motion responses increase as the wave period goes up. However, the pitch motion is not affected significantly by varying wave periods. It may be due to the fact that the low-frequency effects have limited impact on the pitch motion. The strong nonlinearity at extremely large wave amplitude will be the task in our near future study.